Rest-to-rest attitude maneuvers of a satellite with flexible solar panels by using input shapers - Parman, Setyamartana; Koguchi, Hideo (Computer Assisted Methods in Engineering and Science, 2023)
A hybrid system of coordinates and a relatively general Lagrangian formulation for studying the dynamics and control of spacecraft with flexible members is developed. Versatility of the formulation is illustrated through a dynamical study of the satellite with two symmetrical flexible solar panels, where the finite element method is used to describe elastic deformations of solar panels modelled as flat plate structures in bending. The performance of the satellite undergoing roll maneuver is simulated. Results indicate that, under an unshaped input, the maneuvers induce undesirable roll motion of the satellite as well as vibration of the solar panels. A zero vibration input shaper is then applied to reduce the largest magnitude of residua oscillation of roll motion. Once the shaped roll torque input is applied to the satellite, the performance improves significantly. When the longest distance of impulsing time sequences in the input shaper is close enough to the period of large amplitude vibration of flexible members, its maximum deflection during attitude maneuver will also be close enough to the amplitude of vibration with this period under the bang-bang input.